2012
DOI: 10.1089/dia.2011.0255
|View full text |Cite
|
Sign up to set email alerts
|

A Minimally Invasive System for Glucose Area Under the Curve Measurement Using Interstitial Fluid Extraction Technology: Evaluation of the Accuracy and Usefulness with Oral Glucose Tolerance Tests in Subjects With and Without Diabetes

Abstract: The glucose AUC monitoring system using IG provided good estimates of reference PG-AUC and maximum PG level during OGTTs in subjects with and without diabetes. This system provides easy-to-use monitoring of glucose AUC, which is a good indicator of postprandial glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…In accordance with a previous study, 15 good correlation was confirmed between peak PG levels and IG AUC or PG AUC (R = 0.87 for IG AUC and R = 0.96 for PG AUC in Figures 5A and 5B), suggesting that peak glucose levels can be detected simply and precisely by MIET without blood sampling. The strong correlation between IG AUC and PG levels at 1 h (R = 0.86) indicated that the time of peak PG level occurred mostly at 1 h after glucose loading (Figure 5C), explaining the weaker correlation between IG AUC and PG levels at 2 h (R = 0.82; Figure 5D).…”
Section: Correlation Between Interstitial Fluid Glucose Area Under Thsupporting
confidence: 92%
“…In accordance with a previous study, 15 good correlation was confirmed between peak PG levels and IG AUC or PG AUC (R = 0.87 for IG AUC and R = 0.96 for PG AUC in Figures 5A and 5B), suggesting that peak glucose levels can be detected simply and precisely by MIET without blood sampling. The strong correlation between IG AUC and PG levels at 1 h (R = 0.86) indicated that the time of peak PG level occurred mostly at 1 h after glucose loading (Figure 5C), explaining the weaker correlation between IG AUC and PG levels at 2 h (R = 0.82; Figure 5D).…”
Section: Correlation Between Interstitial Fluid Glucose Area Under Thsupporting
confidence: 92%
“…Microneedles are used for extraction of interstitial fluid prior to ex-vivo measurement. [20][21][22] El-Laboudi et al have outlined the state-of-the-art in the use of microneedles as biosensors for glucose monitoring. 19 Interest in mHealth (mobile health) apps and devices is soaring, generating a huge social appetite and financial market for wearable sensors.…”
Section: Evolution Of Microneedle Biosensorsmentioning
confidence: 99%
“…Systems containing microneedle arrays have previously been developed for sampling of analytes in transdermal blood and/or interstitial fluid [18][19][20] . For instance, systems containing microneedles arrays have been developed for detection of glutamate [21] , glucose [22,23] , and potassium ions [24] . In this study, microneedle arrays were used as a sampling mechanism for detection of histamine in fish flesh.…”
Section: Introductionmentioning
confidence: 99%